Bibliographic review of the mode of road transportation in Brazil (Research, Society and Development, 2019)
Brazil needs an adequate and well-planned transport infrastructure, since it is necessary to coordinate transport modes and 61% of the total cargoes are transported by road (CNT, IBGE 2017). This is also the segment that uses the most, and the one that has the largest share in the wealth production of the sector. These factors make the behavior of the transport and logistics sector influenced by the performance of the Brazilian road network. Therefore, the objective of this article is to perform a bibliographic review, producing a critical analysis, in relation to the mode of road transport in Brazil, between the years 2010 and 2017. For this, an exploratory study of newsletters, statistical data and reports published by ANTT, CNT, IBGE and PRF. Therefore, it has been found that it is common from an uncontrollable demand, the occurrence of problems such as congestion, inefficiency, accidents and high costs. Thus, the modal performance is a reflection of an efficient investment in infrastructure and road maintenance, which reduces the costs of accidents, since the investment is intrinsically related to the country's economy.